A Major Role for the Lateral Habenula in Depressive Illness: Physiologic and Molecular Mechanisms - Gold, Philip W.; Kadriu, Bashkim (Frontiers in Psychiatry, 2019)
Emerging preclinical and clinical evidence indicate that the lateral habenula plays a major role in the pathophysiology of depressive illness. Aberrant increases in neuronal activity in the lateral habenula, an anti-reward center signals down-regulation of brainstem dopaminergic and serotonergic firing, leading to anhedonia, helplessness, excessive focus on negative experiences and hence, depressive symptomatology.The lateral habenula has distinctive regulatory adaptive role to stress regulation in part due to its bidirectional connectivity with hypothalamic-pituitary-adrenal (HPA) axis. In addition, studies show increased lateral habenula activity also drives rapid eye movement (REM) sleep, and decreases REM latency, both characteristics of depressive illness. Lack of perceived reward experienced during the adverse outcomes also precipitates lateral habenula firing, while outcomes that meet or exceed expectations decrease lateral habenula firing and, in turn, increase midbrain dopaminergic and serotonergic neurotransmission. The ability to update expectations of the environment based on rewards and aversive stimuli reflects a potentially important survival mechanism relevant to the capacity to adapt to changing circumstances. What if one lives in a continuously aversive and invalidating environment or under the conditions of chronic stress? If there is a propensity of the habenula to release many burst discharges over time, an individual could habitually come to perceive the world as perpetually disappointing. Conceivably, the lateral habenula could learn to expect an adverse outcome systematically and communicate it more easily. Thus, if the lateral habenula fires more frequently, it may lead to a state of continuous disappointment and hopelessness, akin to depression. Furthermore, postmortem studies reveal that the size of the lateral habenula and total number of neurons is decreased in patients who had depressive illness. Novel research in the field shows that ketamine induces rapid and sustained antidepressant effect. Intriguingly, recent preclinical animal models show that ketamine abolishes N-methyl-D-aspartate receptor (NMDAR)-dependent lateral habenula bursting activity, leading to rapid resolution of depressive symptoms.